Activation of interferon-α signaling by resveratrol, genistein and quercetin - O. A. Vlasova; A. A. Borunova; A. Safina; I. V. Smetanina; E. A. Lesovaya; G. A. Belitsky; T. N. Zabotina; K. Gurova; K. I. Kirsanov; M. G. Yakubovskaya (Сибирский онкологический журнал)
Resveratrol, genistein and quercetin from the group of polyphenols from secondary plant metabolites reveal cancer preventive and antivirus effects realized via their pleiotropic influence on the different macromolecules in cells. These compounds can interact with DNA without the formation of covalent bonds. This process is usually followed by changes in spatial, physical-chemical and structural DNA characteristics that can result in disfunction of DNA metabolism enzymes and chromatin destabilization. Similar effects were described for anticancer drug Curaxine CBL0137 in association with activation of interferon-α signaling. We demonstrated dose-dependent stimulating effects of resveratrol, genistein and quercetin on interferon-α signaling using HeLa cells expressed mCherry protein with interferon-stimulated response elements (ISRE) in promoter. Furthermore, it was shown by live-cell fluorescent microscopy in HT1080 cells with mCherry-labeled histone H1.5 that described polyphenols induced the redistribution of this linker histone in cell nuclei. The data obtained suggest an existence of DNA-dependent mechanism of anticancer effects of plant polyphenols and a need for further study of crosslinks between the polyphenols’ influence on chromatin structure and the changes in genome function, in particular, induction of interferon- interferon-α signaling.